The Role of Village Heads in Motivating Drug Users in Palong Village, Pidie Regency - Armiwal; Thaib, Anwar; Ramadhani, Syahrul (Dinasti Publisher, 2023)
In an effort to obtain provisions for drug users who have the motivation not to return to their